KOMUNIKASI AGAMA DI DUNIA VIRTUAL: KAJIAN TERHADAP FANPAGE SANTRIONLINE - Setiyawati, Anis; Sofian, Akhriyadi; Parmudi, Mochamad (JSW (Jurnal Sosiologi Walisongo), 2019)
Facebook is one of the social media (socmed) platform that?s famous to people globally. Facebook has a Fanpage that can accommodate limitless friendship. Millenials of santri are also Fanpage users. Fanpage Santrionline is a media used to communicate amongst santri Nusantara. This article based on qualitative research with a descriptive analysis approach. Its research method was virtual ethnography and cyber media analysis. This analysis method consists of four levels: first, media space level, that used by santri to communicate, learn Islam, and do business. Second, the media archive level is an alternative narration to communicate a peaceful message. Third, media object level, media to interactive communication amongst the communities. Fourth, experiential stories, and experience to learn Islam amongst the followers of Fanpage Santrionline.